PHYSICAL PERFORMANCE AND BODY COMPOSITION IN MAINTENANCE HEMODIALYSIS (MHD) PATIENTS - M Zhang; JC Kim; BB Shapiro; Y Li; R Bross; K Kalantar-Zadeh; U Feroze; J Porszasz; JD Kopple (The Korean Society of Nephrology, 2012)
MHD patients (pts) often display protein-energy wasting, sarcopenia & diminished physical performance. This study was undertaken to assess the relationship between body composition & physical performance in MHD pts. Methods: Body composition, assessed by dual energy x-ray absorptiometry and body mass index (BMI), were compared to 3 measures of physical performance: 6-minute walking distance (6-MW), sit-to-stand testing and stair climb. 52 clinically stable MHD pts (≥6 mo) and 21 matched normal controls were examined in this ongoing study. Results: Pts were 53±13SD yrs, 33% female; 38% diabetic; dialysis vintage was 62±52 months. Normals were 52 years and 43% female. MHD pts had higher % body fat than Normals. 6-MW and sit to stand cycles were much lower in MHD men and women than in Normal men and women. 6MW in MHD and Normals were 445 vs 630 meters, respectively (p<.001). In men but not women, time to climb 22 stairs was greater in MHD pts then in Normals (p=.03). Unadjusted analyses in MHD indicated that 6-MW distance correlated negatively with lean body mass index (LBMI, kg of LBM/m2; r=-0.37; p<0.01) and % body fat (r=-0.33; p= 0.02); stair climb time correlated negatively with lean leg mass (r=-0.32, p=0.03) and total leg mass (r=-0.29, p=0.045).). Sit-to-stand did not correlate with any body composition measure. 6-MW adjusted for age and gender correlated negatively with LBMI (r=-0.29; p=0.04).There were no associations between BMI (range, 19.8-44.2 kg/m2) and physical performance. Conclusions: These findings indicate that adult MHD pts had a higher % body fat. Measures of physical performance were markedly reduced in MHD pts as compared to Normals. Physical performance in MHD, measured especially by 6-MW, correlated negatively with some measures of body composition, particularly with LBMI.